Performance of budget execution in projects of local governments in the region, periods 2019 -2021 Peru - Copari Condori, Sara (2023)
The research addresses the budget execution process, whose objective was to measure the level of budget execution for local government projects in the Puno region in the periods 2019 to 2021, with a quantitative, non-experimental methodology with a crosssectional descriptive research design applied For the 110 local governments, a documentary analysis sheet was used to identify the level of expenditure execution, using the MEF range: (84-00=deficient) (89-85 =regular) (94-85=good) ( 100-95=Very good), the institutional performance is qualified according to the range, where the following result was obtained: the average execution of public spending in projects of the municipalities in periods 2019 to 2021, is deficient; it is below and equal to 84% of the budget execution efficiency level. In the 2019 period, the average execution of project spending is 70.4% as of December 31, in 2019, 61.2% in the 2020 period as of December 31, in the 2021 period, 73.0% of the fiscal year. Despite the COVID 19 pandemic, so evident in 2020 and 2021, the execution of the budget for goods and services for the benefit of the population continues with limitations the same as in 2019.